Characteristics of Glass Materials that Influence the Level of Thermal Comfort and Building Energy Consumption - Ayuningtyas, Nurina Vidya; Iskandar, N; Suryabrata, J A (Jurnal Teknik Sipil dan Perencanaan, 2019)
Energy requirements are increasing rapidly. The building sector is one of the world's largest energy consumers. The proportion ranges from 10-15 percent in developing countries and more than 40 percent in developed countries. Building is designed to accommodate human activities should apply designs that are able to minimize the amount of energy consumption during the construction process and when the building is operating and occupied. The simulation process in this study was computerized with the help of the main software used was EnergyPlus v8.1 and version 0.7 of Open Studio plugins that were run on Google Sketchup v7.0 software. Simulation is only done on one typical floor in the position in the middle of the total height of the building. The dimensions of this hypothetical floor are 40m x 40m with floor to floor 4.2 m height and floor to ceiling 2.8 m. This model is expected to represent the typical office building. The amount of energy consumption in this building is indirectly derived from the design of the building envelope. The results of this study indicate the greater the value of Solar Heat Gain Coefficient (SHGC), the greater the heat radiation from sunlight that will enter the building / room. The results in higher temperatures in the room and higher energy consumption in the building. Every decrease in SHGC is 0.2, it will increase energy consumption by approximately 9 kWh / m2. In addition, to achieve the thermal comfort of occupants by doing a decrease in room temperature settings it will also have an impact on the amount of energy consumption. The increase in energy consumption of each Air Temperature is lowered by 1Ã‚Â°C by 3.44 kWh / m2.Ã‚Â